2020
DOI: 10.5194/amt-2019-465
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of particle size magnifier inversion methods to obtain particle size distribution from atmospheric measurements

Abstract: Abstract. Determining the particle size distribution of atmospheric aerosol particles is an important component to understand nucleation, formation and growth. This is particularly crucial at the sub 3 nm range because of the growth of newly-formed nanoparticles. The challenge in recovering the size distribution is due its complexity and the fact that not many instruments currently measure at this size range. In this study, we used the particle size magnifier (PSM) to measure atmospheric aerosols. Each event w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Traditionally, NPF events occur during the time window between sunrise and sunset by photochemical reactions Dada et al, 2018). The binary or ternary nucleation between sulfuric acid and water, ammonia, or amines are usually thought of as sources of atmospheric cluster mode particles, espe-cially in heavily polluted environments Yao et al, 2018;Chu et al, 2019). The burst of cluster mode particle number concentration outside the traditional NPF time window, especially during the rush hour in the afternoon, suggests a very different source of cluster mode particles from traditional nucleation, e.g., nucleation from gases emitted by traffic (Rönkkö et al, 2017).…”
Section: Diurnal Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, NPF events occur during the time window between sunrise and sunset by photochemical reactions Dada et al, 2018). The binary or ternary nucleation between sulfuric acid and water, ammonia, or amines are usually thought of as sources of atmospheric cluster mode particles, espe-cially in heavily polluted environments Yao et al, 2018;Chu et al, 2019). The burst of cluster mode particle number concentration outside the traditional NPF time window, especially during the rush hour in the afternoon, suggests a very different source of cluster mode particles from traditional nucleation, e.g., nucleation from gases emitted by traffic (Rönkkö et al, 2017).…”
Section: Diurnal Behaviormentioning
confidence: 99%
“…Apart from their health effects, the temporal and spatial variation of particle number concentrations of different sizes is a good indicator of the strength of their emission sources. Aerosols are emitted directly as primary particles, such as sea salt or dust particles; as a result of natural phenomena (Solomos et al, 2011); or they can be formed through new particle formation (Kulmala, 2003;Kulmala et al, 2004Kulmala et al, , 2013Kerminen et al, 2018;Chu et al, 2019). Newly formed particles can grow up to diameters of 20-100 nm within a day (Kulmala et al, 2004), and they have been found to contribute to a major fraction of the global cloud condensation nuclei (CCN) population, thus indirectly affecting the climate .…”
Section: Introductionmentioning
confidence: 99%
“…Before the PSM raw data was inverted, the data was run through a quality control algorithm in which we assumed that the measured total concentration during each scan should have a positive and statistically significant (p < 0.05) correlation with the PSM saturator flow rate (Chan et al, 2020). Increasing the flow rate should always result in increased total concentration because we are activating a larger size range of particles.…”
Section: Psm Data Analysismentioning
confidence: 99%
“…The two most popular methods to invert PSM data are the kernel function method and the step inversion method. The expectation-maximization (EM) method has been recently recommended over the kernel method because it is less sensitive to random errors (Cai et al, 2018;Chan et al, 2020). Here, we compare the kernel method and the EM method using PSM data from the whole measurement period.…”
Section: Ncnc (Psm+cpc) Inversionmentioning
confidence: 99%
“…4) Noise filtering procedure achieved by applying a 6 th order median filter on the one second resolution data. 5) Quality check using the method suggested by Chan et al (2020). 6) Minimization of the inversion matrix using a saturator flow inversion window of 0.08 lpm which minimized the saturator flow (corresponding to cut-off diameter) scans from ~120 to 16 per onedirection of the scan.…”
Section: Ncnc (Psm+cpc) Inversionmentioning
confidence: 99%